Transformation of the sanctity marriage amidst high divorce cases in Denpasar district court - Vijayantera, I Wayan Agus; Hengki, I Gusti Bagus; Permadhi, I Putu Lantika Oka (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The Marriage Law, which fundamentally aims to make divorce difficult, when confronted with the reality of a high divorce rate in the Denpasar District Court, indicates concerns about the erosion of the sanctity of marriage. This transformation of the sanctity of marriage towards an undesirable direction is undoubtedly worrisome. Stemming from this issue, the research aims to analyze the sanctity of marriage and the role of the judicial system in preserving the sanctity of marriage by preventing and complicating divorce. This research employs empirical legal research methods. The procedures involve collecting data consisting of factual or social phenomena and legal norms. Primary data collection includes observation to gather data on divorce cases, followed by interviews with informants who are judges at the Denpasar District Court and lawyers who have litigated at the same court. Additionally, a questionnaire was administered to 29 respondents through a focus group discussion. In addition to primary data, the study also collects secondary data derived from legal regulations and related literature. The collected data is then analyzed using qualitative techniques to provide sound arguments in analyzing the research issues. The research findings indicate that the sanctity of marriage originates from its validation based on religious and cultural customs. The bitter reality of the high number of divorce cases in the Denpasar District Court suggests a decline in the understanding of marriage sanctity. To optimize marital sanctity, three solutions are proposed in this study: maximizing the role of judges at the Denpasar District Court in earnestly preventing divorce in every session, reforming mediation regulations to make them mandatory without exceptions, and fostering societal efforts to understand the importance of preserving marital sanctity.